Biological Effects of Low Level Laser Therapy - Farivar, Shirin; Malekshahabi, Talieh; Shiari, Reza (Journal of Lasers in Medical Sciences, 2014)
The use of low level laser to reduce pain, inflammation and edema, to promote wound, deeper tissues and nerves healing, and to prevent tissue damage has been known for almost forty years since the invention of lasers. This review will cover some of the proposed cellular mechanisms responsible for the effect of visible light on mammalian cells, including cytochrome c oxidase (with absorption peaks in the Near Infrared (NIR)). Mitochondria are thought to be a likely site for the initial effects of light, leading to increased ATP production, modulation of reactive oxygen species, and induction of transcription factors. These effects in turn lead to increased cell proliferation and migration (particularly by fibroblasts).